René Maran lecteur de Charles Darwin et Rémy de Gourmont - Roseline Garcia Ballester (Continents manuscrits)
The richness of René Maran’s work hasn’t been fully discovered so far. The study of the novels, poetry and letters of René Maran to Manoel Gahisto shows the importance of Charles Darwin in René Maran’s thought.